Vienna Philharmonic directed by Hans Knappertsbusch, February 17, 1941 - Wiener Philharmoniker::::::::::::::: (Germany; Hamburg; Gebrüder Lüdeking, 2020)
Program of a concert by the Vienna Philharmonic directed by Hans Knappertsbusch, February 17, 1941, in Hamburg, Germany. The concert included Beethoven's Seventh Symphony, op. 92. Also includes an announcement of a concert on Feb. 19 by the Havemann-Quartett from Berlin, performing Beethoven's String Quartet in E-flat Major, op. 74.